Comparative Effects of Graphene and Molybdenum Disulfide on Human Macrophage Toxicity. Issue 35 (2nd August 2020) - Lin, Hazel; Ji, Ding‐Kun; Lucherelli, Matteo Andrea; Reina, Giacomo; Ippolito, Stefano; Samorì, Paolo; Bianco, Alberto
Abstract: Graphene and other 2D materials, such as molybdenum disulfide, have been increasingly used in electronics, composites, and biomedicine. In particular, MoS2 and graphene hybrids have attracted a great interest for applications in the biomedical research, therefore stimulating a pertinent investigation on their safety in immune cells like macrophages, which commonly engulf these materials. In this study, M1 and M2 macrophage viability and activation are mainly found to be unaffected by few‐layer graphene (FLG) and MoS2 at doses up to 50 µg mL −1 . The uptake of both materials is confirmed by transmission electron microscopy, inductively coupled plasma mass spectrometry, and inductively coupled plasma atomic emission spectroscopy. Notably, both 2D materials increase the secretion of inflammatory cytokines in M1 macrophages. At the highest dose, FLG decreases CD206 expression while MoS2 decreases CD80 expression. CathB and CathL gene expressions are dose‐dependently increased by both materials. Despite a minimal impact on the autophagic pathway, FLG is found to increase the expression of Atg5 and autophagic flux, as observed by Western blotting of LC3‐II, in M1 macrophages. Overall, FLG and MoS2 are of little toxicity in human macrophages even though they are found to trigger cell stress and inflammatory responses. Abstract : As graphene and molybdenum disulfide have been increasingly used in biomedical research, it is important to check their safety in immune cells. Primary human macrophage viability and activation are unaffected by both materials, even though they can trigger cell stress and inflammatory responses.